Phenotypic plasticity in the energy metabolism of a small Andean rodent: Effect of short-term thermal acclimation and developmental conditions - Menéndez, Josefina (2021)
The study of phenotypic variation within species in response to different environments is a central issue in evolutionary and ecological physiology. Particularly, ambient temperature is one of the most important factors modulating interactions between animals and their environment. Phyllotis xanthopygus, a small Andean rodent, exhibits intraspecific differences along an altitudinal gradient in traits relevant to energy balance that persist after acclimation to common experimental temperatures. Therefore, we aim to explore geographic variations in energetic traits of P. xanthopygus and to assess the contribution of phenotypic plasticity to population differences. We compared metabolic rate and thermal conductance in response to different acclimation temperatures in animals collected at distinct altitudes (F0 generation) and in their offspring, born and raised under common-garden conditions (F1 generation). We found intraspecific differences in resting metabolic rate (RMR) of animals collected at different altitudes that were no longer evident in the F1 generation. Furthermore, although both generations showed the same pattern of RMR flexibility in response to acclimation temperature, its magnitude was lower for the F1 individuals. This suggests that developmental conditions affect the short-term acclimation capacity of this trait during adulthood. On the other hand, thermal conductance (C) showed irreversible plasticity, as animals raised in the laboratory at stable warm conditions had a relatively higher C than the animals from the field, showing no adjustments to thermal acclimation during adulthood in either group. In sum, our results support the hypothesis that the developmental environment shapes energetic traits, emphasizing the relevance of incorporating ontogeny in physiological studies.